Smothering the Right to Protest: The #Endsars 2020 Protest in Perspective - Ogwuda, Ebele Gloria (ABUAD Law Journal, 2025)
Protests play a pivotal role in the civil, political, economic, social and cultural life of societies as it often and continue to inspire positive change and improve protection of human rights. It provides a platform for citizens to hold the government accountable by demanding better treatment. The #EndSARS social movement which started in 2017 was rekindledin 2020 to inter aliascrap the Special Anti-robbery Squad (SARS), end police brutality, extra judicial killings, etc. What however started off as a peaceful protest across the country became bloody when on 20th of October, 2020, the government allegedly deployed security personnel to peaceful, unarmed and unsuspecting protesters at the Lekki Toll Gate area of Lagos metropolis (the convergence point for the protesters). An act which appeared to be premeditated left scores dead. This action leaves us in doubt as to the ‘existence’ of the right to protest in Nigeria. It is against this background that the paper examines the right to protest in Nigeria vis-à-vis the #EndSARS protest and the resultant effect. This is done to ascertain the extent of the right and government’s responsibility towards protecting this right. Using the doctrinal approach, the paper finds that the brutal hijack/killings of the non-violent protests/protesters by state actors was an outright violation of the right to protest and clearly an act of failure by the government to ensure security and welfare of the people as provided under section 14(2)(b) of the 1999 Constitution. The paper concludes with recommendations calling on the government to adopt proactive measures to ensure effective policing of protests through a non-violent control strategy that protects and also prevents violation of this right.